(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Martial law is one of the most controversial periods in the post-WWII history of Poland. Introduced on December 13, 1981 it ended the 16-month-long “festival of Solidarity”. Official reasons for its imposition were to prevent further degradation of Poland’s economy and social structures, but a threat of Soviet military intervention was also suggested. The opposition activists perceived it as an attempt of the totalitarian regime to save its falling position with the use of most brutal methods, unknown in Poland since the Stalinist period. The article is based on the analysis of contemporary Polish school history textbooks for all levels of education. It aims to present the strategies adopted by the textbook authors to deal with this controversial issue. The author will attempt to find answers to the following questions: Do the text book authors notice the controversies? Do they show one or more points of view? Do they ask students about their own opinions or about the opinions of their friends or relatives? Are the textbooks open for different interpretations or do they, explicitly or implicitly, prefer only one? How emotional is the text and other materials? How have the textbooks changed since the collapse of the communist regime in 1989?